Ammonia excretion by tambaqui (Colossoma macropomum) related to water temperature and fish mass - Orbe, Rosa Angélica Ismiño; Lima, Carlos Alberto Rego Monteiro Araujo; Gomes, Levy de Carvalho (Pesquisa Agropecuaria Brasileira, 2003)
Ammonia, an excretion product of fish, is toxic to aquatic organisms. The objective of this study was to account daily ammonia excretion rates of tambaqui (Colossoma macropomum), the main fish species of the Amazonia related to water temperature and fish mass. Ammonia excretion rates were measured every two hours during a 24-hour period and results were evaluated by a multiple linear regression. Tambaqui presented two to five excretion peaks during the 24-hour period, reaching up to ten times the mean excretion rates. The model developed by the multiple linear regression explained 95.2% of the daily ammonia excretion rates, which increased according to fish mass and decreased when water temperature increased.
Keywords: water quality; rearing environment; nitrogen products; weight; protein